2022
DOI: 10.1016/j.socscimed.2022.114716
|View full text |Cite
|
Sign up to set email alerts
|

Sex disparities in COVID-19 outcomes in the United States: Quantifying and contextualizing variation

Abstract: This paper presents the first longitudinal study of sex disparities in COVID-19 cases and mortalities across U.S. states, derived from the unique 13-month dataset of the U.S. Gender/Sex COVID-19 Data Tracker. To analyze sex disparities, weekly case and mortality rates by sex and mortality rate ratios and rate differences were computed for each U.S. state, and a multilevel crossed-effects conditional logistic binomial regression model was fitted to estimate the variation of the sex disparity in mortality over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
55
2
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 62 publications
7
55
2
7
Order By: Relevance
“…Our study adds to increasing evidence indicating that COVID-19 sex disparities cannot solely be explained by sex-specific biological mechanisms and are also explained by gendered or sex-specific patterns in health behaviors, contextual factors, and pre-existing health conditions. (7) In line with this notion, sex hormone status, hormone replacement, or hormone deprivation therapies were not associated with PASC in either sex in our study, although it has recently been proposed that the symptoms of PASC may overlap with those of perimenopause. (32) Similarly, psychosocial and behavioral factors and their interaction with sex/gender remained amongst the strongest predictors of PASC, even when only hospitalized patients were analyzed who, amongst all study groups, were best characterized regarding biological (clinical and laboratory) variables.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our study adds to increasing evidence indicating that COVID-19 sex disparities cannot solely be explained by sex-specific biological mechanisms and are also explained by gendered or sex-specific patterns in health behaviors, contextual factors, and pre-existing health conditions. (7) In line with this notion, sex hormone status, hormone replacement, or hormone deprivation therapies were not associated with PASC in either sex in our study, although it has recently been proposed that the symptoms of PASC may overlap with those of perimenopause. (32) Similarly, psychosocial and behavioral factors and their interaction with sex/gender remained amongst the strongest predictors of PASC, even when only hospitalized patients were analyzed who, amongst all study groups, were best characterized regarding biological (clinical and laboratory) variables.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with our conclusion, substantial variation in the magnitude and direction of COVID-19 sex disparities across geographical localities, amongst racial and ethnic groups, and over time exists, all of which are better explained by contextual factors than biological variables. (7,33,34) The risk predictors for PASC selected by our models confirm previous reports indicating that psychosocial stress has substantially increased in women during the pandemic. Indeed, women have been disproportionately affected by imposed quarantine and lockdown measures given that typical feminine roles such as parenting, homeschooling, and other caring duties are still predominantly assumed by women.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Although several studies, including ours, observed worse outcomes of COVID-19 in male patients, these data should be interpreted carefully, since several other characteristics might also play a role in the COVID-19 prognosis apart from gender. For instance, a recent report observed a higher mortality rate from COVID-19 in males in USA counties [ 42 ]. However, even before the pandemic, USA men had higher all-cause mortality rates than women [ 42 ], and perhaps COVID-19 did not change this dynamic, since another report observed a similar increase in crude excess in both sexes in 2020 [ 43 ].…”
Section: Discussionmentioning
confidence: 99%